Defining Who You Are By What You're Not: Organizational Disidentification and The National Rifle Association - Elsbach, Kimberly D.; Bhattacharya, C. B. (Organization Science, 2001)
Through two exploratory studies, we develop and test an introductory framework of “organizational disidentification.” Our first study explores the concept of organizational disidentification through a qualitative investigation of cognitive relationships with the National Rifle Association (NRA). Findings suggest that organizational disidentification is a self-perception based on: (1) a cognitive separation between one's identity and the organization's identity, and (2) a negative relational categorization of oneself and the organization (e.g., categorizations such as “rivals” or “enemies”). Organizational disidentification appears to be motivated by individuals' desires to both affirm positive distinctiveness and avoid negative distinctiveness by distancing themselves from incongruent values and negative stereotypes attributed to an organization. Our findings also suggest that organizational disidentification can lead individuals to take action (either volunteer work or voicing their opinion) as a result of their perceived separation from the organization's identity. Results of our second study”a large-scale survey of public attitudes about the NRA”provide support for this framework.